2020
DOI: 10.5530/jyp.2020.12.61
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Herbal Therapy with Leave of Gynura procumbens (Lour.) Merr

Abstract: Plants are important source of traditional medicine that can be used to aid many type of illness. Gynura procumbens is one of the plants that are often used by Indonesian people as traditional medicine. Gynura procumbens exhibits antibacterial, anticancer, anti-hyperglycemic, antihypertensive, anti-inflammatory, antioxidant, cardioprotective, fertility enhancement, organ protective activity. This review aims to provide an overview on the relatedness of the identified bioactive compounds with the reported biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Согласно результатов, полученных в других исследованиях экстракт из стеблей ДП снижает уровень ферментов и накопление липидов в печеночной ткани [14]. В нашем эксперименте интрагастральное введение данного препарата не оказало существенного влияния на показатели липидного спектра, однако привело к значимому уменьшению уровня АСТ в сыворотке лабораторных животных и препятствовало формированию гепатомегалии и характерных для стеатоза морфологических изменений в ткани печени.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Согласно результатов, полученных в других исследованиях экстракт из стеблей ДП снижает уровень ферментов и накопление липидов в печеночной ткани [14]. В нашем эксперименте интрагастральное введение данного препарата не оказало существенного влияния на показатели липидного спектра, однако привело к значимому уменьшению уровня АСТ в сыворотке лабораторных животных и препятствовало формированию гепатомегалии и характерных для стеатоза морфологических изменений в ткани печени.…”
Section: Discussionunclassified
“…В ряде исследований было найдено положительное влияние β-ситостеринов при метаболическом синдроме у пациентов с ожирением [9][10][11][12][13]. По данным литературы экстракт из стеблей ДП снижает уровень ферментов и накопление липидов в печеночной ткани [14].…”
Section: Introductionunclassified
“…It was shown in this study that GP extract supplementation could reduce the level of IL-6, TNF-a, and CRP in postmenopausal rats. A recent study suggested that steroid might be one class of anti-inflammatory compounds that suppressed the expression of inflammatory responses (Jarikasem et al 2013) by inhibiting the vasodilation, increasing vascular permeability that occurred following an inflammatory insult, and decreasing leukocyte migration into the inflamed sites (Timotius and Rahayu 2020).…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…The plant G. procumbens is utilized in traditional medicine for topical application in the treatment of different types of ailments (Krishnan et al, 2015). It is commonly used in treating rash, eruptive-fever, kidney disease, hypertension, migraine, diabetes mellitus, constipation and cancer (Roshida et al, 2009;Algariri et al, 2013;Timotius and Rahayu, 2020). Bioactive compounds such as flavonoids and glycosides were credited to be the active phytochemicals of the specie (Akowuah et al, 2002).…”
mentioning
confidence: 99%
“…The small molecular weight compounds extracted from G. procumbens have been reported to display anti-cancer, antioxidant, antiinflammatory and anti-hyperglycemic activities. The benefits of the traditional use of G. procumbens have also been supported by the identification of several active chemical constituents including flavonoids (kaempferol, rutin and quercetin), chlorogenic acids, phenolics and steroids (Timotius and Rahayu, 2020). Gynura procumbens is a new source of potential herbs in the herbal industry.…”
mentioning
confidence: 99%